IMPROVING THE STUDENTS’ WRITING NARRATIVE TEXT BY APPLYING COOPERATIVE INTEGRATED READING AND COMPOSITION TECHNIQUE - MarhamahMelisda; Anni Holila Pulungan (Universitas Negeri Medan, 2014)
This study concerrns with Improving the Students Writing Narrative Text by ApplyingCooperative Integrated Reading and Composition Technique.The objective was toinvestigate improvement of students’ writing narrative text by applying CooperativeIntegrated Reading and Composition Technique. This research was conducted by usingaction research method. The subject of the study was grade VIII students of MTS Al-Hasanah Medan totalling to 29 students. They were taught writing by cooperativeintegrated reading and composition technique. The instruments for collecting data werequantitative data and qualitative data (observation sheet, questionnaire sheet, andinterview sheet). Based on the test score of quantitative data, students’ score keptimproving in every evaluation. In the orientation test the mean was 43, 2, in the cycle Itest the mean was 55, 6. In the cycle II test the mean was 67.2. The percentage oforientation test was 10, 34%, cycle I test was 24, 13% and cycle II test was 86, 20%.The finding of the research showed that applying Cooperative Integrated Reading andComposition Technique significantly improved students’ writing. The qualitative datashow that the students were more interested and motivated on writing throughcooperative integrated reading and composition technique. It is suggested that teachersshould apply cooperative integrated reading and composition technique as one ofmethods to improve students’ writing.